PENGARUH PENGGUNAAN ENERGI TERBARUKAN BUTANOL TERHADAP PENURUNAN EMISI JELAGA MESIN DIESEL INJEKSI LANGSUNG BERBAHAN BAKAR BIODIESEL CAMPURAN SOLAR DAN JATROPA (Infotekmesin, 2019)
Diesel engines are widely used as driving forces in vehicles and industry due to fuel efficiency and high output power. The wide use of diesel engines triggers an increase in fuel consumption and exhaust emissions that are harmful to health. Jatropha is a renewable fuel as a solution to increase fuel consumption. However, the high viscosity and low calorific value result in reduced performance and increased exhaust emissions. Butanol has a high oxygen content and cetane number and low viscosity compared to diesel and jatropha. Addition of butanol is possible to reduce the decrease in performance and exhaust emissions of diesel engines. this study evaluates the effect of butanol on reducing Isuzu 4JB1 diesel engine direct injection emissions. Percentage of blend used 70/30/0, 65/30/5, 60/30/10, and 55/40/15 based on volume. Tests are carried out at 2500 constant turns with a loading of 25% to 100% using the EGR system. The experimental results showed the presence of butanol caused a decrease in soot emissions produced by diesel engines